2005
DOI: 10.1093/nar/gki266
|View full text |Cite
|
Sign up to set email alerts
|

Human base excision repair enzymes apurinic/apyrimidinic endonuclease1 (APE1), DNA polymerase   and poly(ADP-ribose) polymerase 1: interplay between strand-displacement DNA synthesis and proofreading exonuclease activity

Abstract: We examined interactions between base excision repair (BER) DNA intermediates and purified human BER enzymes, DNA polymerase β (pol β), apurinic/apyrimidinic endonuclease (APE1) and poly(ADP-ribose) polymerase-1 (PARP-1). Studies under steady-state conditions with purified BER enzymes and BER substrates have already demonstrated interplay between these BER enzymes that is sensitive to the respective concentrations of each enzyme. Therefore, in this study, using conditions of enzyme excess over substrate DNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 48 publications
3
70
0
2
Order By: Relevance
“…Although these results comply with the suggested function of human UDG in controlling the rate of BER (71), our findings provide, to our knowledge, the first evidence of an important role of UDG in determining the BER subpathway. The T. acidophilum genome (51) contains neither a gene homologue to the XRCC1 (UniProtKB/Swiss-Prot accession number P18887) gene nor a gene homologue to a gene encoding a putative PARP1 or 2 protein (UniProtKB/Swiss-Prot accession numbers P09874 and Q9UGN5, respectively), which also has been suggested as a possible mammalian repair recruiter and regulator (15,20,67), so perhaps this organism uses UDG itself for such purposes. In this regard, we propose the following working hypothesis consisting of two scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results comply with the suggested function of human UDG in controlling the rate of BER (71), our findings provide, to our knowledge, the first evidence of an important role of UDG in determining the BER subpathway. The T. acidophilum genome (51) contains neither a gene homologue to the XRCC1 (UniProtKB/Swiss-Prot accession number P18887) gene nor a gene homologue to a gene encoding a putative PARP1 or 2 protein (UniProtKB/Swiss-Prot accession numbers P09874 and Q9UGN5, respectively), which also has been suggested as a possible mammalian repair recruiter and regulator (15,20,67), so perhaps this organism uses UDG itself for such purposes. In this regard, we propose the following working hypothesis consisting of two scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that interaction between APE and dRP-containing intermediates could assist in SN-BER versus LP-BER subpathway choice, and a large excess of APE was found to stimulate Pol ␤ strand-displacement synthesis during LP-BER (46). This stimulation was inhibited by the addition of PARP-1 (46).…”
Section: Discussionmentioning
confidence: 99%
“…This localization is abolished in the presence of antioxidants (12), suggesting that ROS are the driving force of this localization. Another interesting APE1 function, connected to its capacity to bind to SSB, is that of inhibiting the same binding by PARP1, with consequent inactivation of the poly-ADP-ribosylation and prevention of necrosis (121).…”
Section: Dna Repair Activity Of Ape1mentioning
confidence: 99%